ANTROPOMETRI & DENVER TEST II TRAINING TO CADRE HEALTH CARE COMMUNITY IN BINONG DISTRICT CURUG TANGERANG - Yenni Ferawati; Deborah Siregar; Ian Rudy Mambu; Dora Samaria; Theresia - (Jurnal Sinergitas PKM & CSR, 2017)
Health care community (Posyandu) is one form of Community Based Health Efforts (UKBM) implemented by, from and within the community to empower and provide convenience to the public to obtain health services for mothers, infants and toddlers. Cadres have the big role in implementing activity in Posyandu such as measuring children weight and height and to see children developmental status until six years old. However, there were few cadres whose done inappropriate weight and height measurement during posyandu. They were not encouraging the children to be in minimal clothes and not using sandals during the measurement. The cadres were also not knowing the right way of using Dacin (weight measurement for toddlers). Moreover, cadre were also not aware of the need of developmental status detection. They were never get any training related to those needs. Training of growth and development was done in two days which were attended by 46 cadres from Puskesmas Binong. The training was aimed to improve cadres’ knowledge and skills about children growth and development and how to stimulate the development. There are three activities carried out to achieve the aim. 1. Training of weight and height measurement (Antropometri) 2. Training of Denver test II (tools to detect developmental status) and 3. Workshop of Denver test II assessment. Pre-test and post-test were done before and after the training and the result show there was an improvement in cadres’ knowledge.